Analysis of the quantity and spatial characterization of aluminum in-use stocks in China. (December 2022) - Li, Shupeng; Wang, Zhe; Yue, Qiang; Zhang, Tingan
Abstract: Aluminum is extensively used in construction, infrastructure, transportation, and consumer durables. China's aluminum in-use stocks (AIUS) are rapidly accumulating with accelerated industrialization and urbanization. Although previous research has illustrated AIUS at the national level, a lack of understanding of the spatial patterns of AIUS in China remains. This study used a bottom-up method to calculate the provincial-level spatial distribution of China's AIUS in 2018. The main conclusions are threefold. (1) The total AIUS across the country were 201.21 Tg, approximately 80% deposited in five subsectors, including residential buildings, non-residential buildings, power transmission, passenger cars, and power production. (2) The three regions with the most AIUS were Jiangsu, Shandong, and Guangdong, while the three regions with the least AIUS included Tibet, Hainan, and Qinghai. Per capita aluminum stock decreased from northwest to southeast, varying from 105 to 265 kg/capita. In contrast, the geographic density of AIUS gradually increased from the northwest to the southeast, ranging from 1 to 527 t/km 2 (3) A considerable disparity exists between urban (120 kg/capita) and rural (62 kg/capita) areas regarding the AIUS of buildings, consumer durables, private cars, and motorcycles. This difference illustrates the extreme imbalance between urban and rural social development. The above findings can provide some implications for advancing the management and recycling of aluminum resources. Highlights: China's provincial-level aluminum in-use stocks database for 2018 was developed. The total aluminum stocks were 201.21 Tg, nearly 50% distributed in the building. Densely populated and economically developed areas deposited more aluminum stocks. China's per capita aluminum stock was 144 kg, far behind that of developed countries.